ASEAN regionalism cooperation, values and institutionalization - Roberts, Christopher B. (Routledge security in Asia Pacific series, 2012)
"This book examines the key motivations for and challenges to greater regional integration in Southeast Asia. It covers the full range of issues confronting ASEAN, and discusses both the developments in ASEAN to date and the ones likely to take place in the future."--Publisher's description